1984
DOI: 10.1002/anie.198406381
|View full text |Cite
|
Sign up to set email alerts
|

CP/MAS‐13C‐NMR Spectra of Sclerotized Insect Cuticle and of Chitin

Abstract: Depending on the steric interaction between R' and R2/ R3, 7 decomposes to afford 8 (route @: cleavage of a C-Cl bond) or the butadienes 10 (route @: cleavage of a C-C bond). Spontaneous elimination of CO, and ethyl chloride from 10 lead exclusively to the allenes 9. 4. 11Transallenations have previously hardly played a role in the chemistry of allenes. The novel transallenation method leading to the allene-1,l-dicarboxamides 9["] is widely applicable given the choice of suitable combinations of substituents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…We have found that large quantities of the NBANE present in acidic extracts of the brown cuticle of M. sextu, P. umericanu, and M. dornesticu are not extracted by nonacidic solvents [18], and we are investi-gating the possibility that some of the NBANE in the acidic extracts is actually the hydrolysis product of a covalently bound catecholamine. Peter et al [139] have used cross-polarization magic-angle spinning NMR to examine the structure of moth, locust, and cockroach cuticles. Their spectra show the relative abundance of a rather large number of phenolic and diphenolic carbons, as well as chitin and protein carbons.…”
Section: Interaction Of Diphenols With Other Cuticular Componentsmentioning
confidence: 99%
“…We have found that large quantities of the NBANE present in acidic extracts of the brown cuticle of M. sextu, P. umericanu, and M. dornesticu are not extracted by nonacidic solvents [18], and we are investi-gating the possibility that some of the NBANE in the acidic extracts is actually the hydrolysis product of a covalently bound catecholamine. Peter et al [139] have used cross-polarization magic-angle spinning NMR to examine the structure of moth, locust, and cockroach cuticles. Their spectra show the relative abundance of a rather large number of phenolic and diphenolic carbons, as well as chitin and protein carbons.…”
Section: Interaction Of Diphenols With Other Cuticular Componentsmentioning
confidence: 99%
“…These techniques include: IR spectroscopy (Baxter, Dillon, Taylor, & Roberts, 1992;Brugnerotto et al, 2001;Duarte, Ferreira, Marvão, & Rocha, 2002;Domard & Rinaudo, 1983;Miya, Iwamoto, Yoshikawa, & Mima, 1980;Shigemasa, Matsuura, Sashiwa, & Saimato, 1996a, 1996bSannan, Kurita, Ogura, & Iwakura, 1978;Sabins & Block, 1997); near infrared spectroscopy (NIR) (Rathke & Hudson, 1994); UV-spectrophotometry (Muzzarelli & Rocchetti, 1985;Muraki, Yaku, Iyoda, & Kojima, 1993;Tan, Khor, Tan, & Wong, 1998); ninhydrin assay (Curotto & Aros, 1993;Prochazkova, Värum, & Østgaard, 1999); colloidal titration (Terayama, 1952 Smidrød, 1991a); cross-polarization (CP)/magic-angle spinning (MAS) 13 C NMR (Duarte, Ferreira, Marvão, & Rocha, 2001a;Heux, Brugnerotto, Desbrie'res, Versali, & Rinaudo, 2000;Lamarque, Viton, & Domard, 2004;Peter, Grun, & Forster, 1984;Raymond et al, 1993;Tolaimate et al, 2000); and CP/MAS 15 N NMR (Heux et al, 2000;Yu, Morin, Nobes, & Marchessault, 1999) spectroscopy. Up to date, no review article on the DA determination by various NMR techniques has been published.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of α- and β-chitin are well known (Carlström, 1957; Minke and Blackwell, 1978; Gardner and Blackwell, 1975). Chitin has also been studied extensively in the past by solid-state 13 C NMR spectroscopy (Peter et al, 1984; Schaefer et al, 1987; Fukamizo et al, 1986; Tanner et al, 1990; Andrade et al, 2002; Schmidt-Rohr and Mao, 2002; Cárdenas et al, 2004; Kono, 2004; Kameda et al, 2005; Webster et al, 2006) as well as by Raman and Infrared (IR) spectroscopy (Pearson et al, 1960; Focher et al, 1992; Cárdenas et al, 2004; Yamaguchi et al, 2005). Therefore, these well-established spectroscopic techniques were used within the present work in order to comprehensively characterize the chitin-based scaffold in I. basta skeletons and to monitor its isolation by the alkali-based treatment proposed by Ehrlich et al (2007a).…”
Section: Introductionmentioning
confidence: 99%